Recent Advancement of the Sensors for Monitoring the Water Quality Parameters in Smart Fisheries Farming - Fowzia Akhter; Hasin Reza Siddiquei; Md Eshrat E. Alahi; Subhas C. Mukhopadhyay (Computers, 2021)
Water quality is the most critical factor affecting fish health and performance in aquaculture production systems. Fish life is mostly dependent on the water fishes live in for all their needs. Therefore, it is essential to have a clear understanding of the water quality requirements of the fish. This research discusses the critical water parameters (temperature, pH, nitrate, phosphate, calcium, magnesium, and dissolved oxygen (DO)) for fisheries and reviews the existing sensors to detect those parameters. Moreover, this paper proposes a prospective solution for smart fisheries that will help to monitor water quality factors, make decisions based on the collected data, and adapt more quickly to changing conditions.